The rise in road traffic injuries in Lilongwe, Malawi: A snapshot of the growing epidemic of trauma in low income countries. (2018) - Banza, Leonard Ngoie; Gallaher, Jared; Dybvik, Eva; Charles, Anthony; Hallan, Geir; Gjertsen, Jan-Erik; Mkandawire, Nyengo; Varela, Carlos; Young, Sven
Abstract: Introduction: Road traffic injuries (RTIs) and death are a major public health issue worldwide. Unless appropriate action is taken urgently, the burden of RTIs will continue to increase globally. This will be particularly pronounced in developing countries where rapid motorization is likely to continue over the next decades. Malawi is one of these countries with a population of 17.2 million and a Gross National Income per capita of 340 US$. The impact of the rising burden of injury on the health sector is considerable. However, data to demonstrate this development is lacking. Methods: This study is an analysis of data from the Kamuzu Central Hospital (KCH) Trauma Registry. KCH is a 900-bed tertiary care public hospital in Lilongwe, the capital city of Malawi. The KCH Trauma Registry was established to collect patient demographic information, clinical characteristics, and outcome data for all patients presenting to the emergency department with injuries. All patients who presented to the emergency department with injuries between January 2009 and December 2015 were included in the study. Results: A 96, 967 patients with injuries between 2009 and 2015 were registered in the KCH Trauma Registry. The mean age of these patients was 23.3 years and 36.8% were children younger than 18 years. 25, 193 (26.2%) patients had road traffic related injuries, of these 19, 244 (76.4%) were men. There was a 62.4% rise in the number of RTI victims treated at KCH from 2447 in 2009–3975 in 2015. If this trend continues, 7997 patients will be expected to need treatment for RTIs at KCH in 2030, doubling the numbers seen in 2015 in just 15 years. The highest number of injuries occurred in pedestrians (32.3%) and cyclists (28.2%) and continually rose over the years studied. The length of hospital stay for RTIs increased from 6.4 ± 9.1days in 2009 to 15.0 ± 19.4 in 2015. Discussion: There was a rapidly growing burden of RTIs at KCH in Lilongwe, Malawi, between 2009 and 2015, and projections based on our data show that this burden will double by 2030. It is essential that surgical trauma services are scaled up to meet this challenge in Malawi. There is also a large potential for prevention of injuries involving vulnerable road users. Road traffic campaigns should focus on improved driver training, use of lights, pedestrian and cyclist visibility, and vehicle fitness. Standards should include physical separation of pedestrians and vehicles, through raised pavements or separate walk and cycle ways. The absence of a clear strategy to meet the growing epidemic of injuries in Malawi will come at a huge cost to an already strained economy, and the largest portion of the burden of injury will continue to be borne by the poorest segment of the population. Highlights: Between 2009 and 2015 96, 967 patients with injuries were registered in the KCH Trauma Registry. 25, 193 (26.2%) patients had road traffic related injuries, of these 19, 244 (76.4%) were men. There was a 62.4% rise in the number of RTI victims treated at KCH from 2447 in 2009 to 3975 in 2015. The highest number of injuries occurred in pedestrians (32.3%) and cyclists (28.2%). If the current trend continues, the number of RTI victims treated at KCH could double by 2030.